Preparation method of double-mesoporous zinc metastannate composite gas-sensitive material

Through plasma flame spraying technology, double mesoporous zinc metastanate composite gas-sensitive material is directly prepared without template agent, which solves the problems of pore structure collapse and poor stability of gas-sensitive materials in the prior art, and achieves high efficiency and rapidity gas-sensitive coating preparation and VOC rapid response.

CN119409222APending Publication Date: 2025-02-11YANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411640118.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, after the bimetal oxide gas-sensitive material is calcined to remove organic solvents and template agents, the pore structure collapses due to structural reforming, and its stability is poor, making it difficult to carry out large-scale industrial production.

Method used

The homogeneous mixed solution was prepared by hydrolysis, and the double mesoporous zinc metatinate composite gas-sensitive material was directly prepared by plasma flame spraying technology without template agents. .

Benefits of technology

It realizes the rapid preparation of gas-sensitive coatings without template agents. The coating is fast forming speed, simple method, high binding strength, fast deposition efficiency, bimodal distribution of pore size, and can quickly respond to VOC target gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409222A_ABST
    Figure CN119409222A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-mesoporous zinc metastannate composite gas-sensitive material. The preparation method comprises the following steps: preparing a homogeneous-phase mixed solution by adopting a hydrolysis method; conveying the obtained homogeneous-phase mixed solution to an atomizing nozzle through a gas tank to form liquid drops, and injecting the liquid drops into the center of a plasma flame flow; the plasma flame flow state is controlled by adjusting the hydrogen flow and the arc voltage of the spray gun, so that the liquid material is atomized, evaporated and condensed to form a coating; according to the method, different condensation rates of zinc atoms and tin atoms in the spraying process are utilized, the zinc stannate nano heterojunction can be directly prepared only through one-step solution precursor plasma spraying, no template agent is needed, the coating forming speed is high, the method is simple, the bonding strength is higher, and the deposition efficiency is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material science, and specifically relates to a method for preparing a double-mesoporous zinc metastannate composite gas-sensitive material. Background Art

[0002] Metal oxide semiconductor nanomaterials have a wide range of applications in catalysis, sensing, and energy storage due to their unique micro-nanostructures and special optical and electronic properties. In terms of gas sensing, the rapid diffusion of guest molecules and the large exposure of active sites will greatly improve the performance of gas sensors based on metal oxide semiconductor materials. Therefore, compared with non-porous bulk metal oxide semiconductors, mesoporous metal oxide semiconductors have attracted widespread attention from researchers due to their highly crystallized pore walls, high specific surface area, large pore volume, rich and connected pore structure, and adjustable pore size.

[0003] The gas sensing performance of metal oxide semiconductors is not only related to their pore structure and specific surface area, but also depends on their chemical structure and skeleton composition. The presence of heterostructure complexes in bimetallic oxides can effectively increase the defect sites of metal oxides and increase the concentration of surface adsorbed oxygen. It helps to accelerate the conduction rate of electrons in the skeleton and reduce the activation energy of surface reactions. The construction of heterostructures is considered to be an effective way to improve the gas sensing performance of metal oxide semiconductor materials.

[0004] In the prior art, an invention patent entitled "A method for synthesizing a large-aperture mesoporous bimetallic oxide semiconductor gas-sensitive material" with a publication number of CN 110451561 A and a publication date of November 15, 2019 is disclosed. In this method, a volatile polar organic solvent and a template are co-assembled to form a mesoporous bimetallic oxide, and a step-by-step calcination strategy is used to obtain a semiconductor gas-sensitive material. However, during the post-treatment process of calcining to remove the organic solvent and the template and crystallizing the pore wall of the mesoporous metal oxide, the metal oxide will collapse due to the drastic structural rearrangement, and its poor stability makes it difficult to carry out large-scale industrial production. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above-mentioned and / or existing problems in the prior art in the preparation of bimetallic oxide gas-sensitive materials, the present invention is proposed and used.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a dual-mesoporous zinc metastannate composite gas-sensitive material, comprising the following steps: A homogeneous mixed solution is prepared by a hydrolysis method; The homogeneous mixed solution is transported to the atomizing nozzle through a gas tank, and then injected into the center of the plasma flame after forming droplets; The plasma flame state is controlled by adjusting the hydrogen flow rate and the arc voltage of the spray gun, so that the liquid material is atomized, evaporated and condensed in sequence to form a coating.

[0008] As a preferred scheme for the preparation method of the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the step of preparing a homogeneous mixed solution is to dissolve two metal oxide precursor liquids, metal nitrate and metal chloride, in deionized water according to a set ratio, and stir at room temperature to obtain a homogeneous mixed solution.

[0009] As a preferred solution of the method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the molar ratio of the metal nitrate to the metal chloride is 1:1.

[0010] As a preferred solution of the method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the metal nitrate and the metal chloride are zinc nitrate hexahydrate and tin tetrachloride pentahydrate respectively.

[0011] As a preferred scheme for the preparation method of the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the flow rate of the homogeneous mixed solution when transported to the atomizing nozzle is 28 mL / min, the argon flow rate is 35 L / min, the hydrogen flow rate is 1-5 L / min, and the spraying current is 312 A.

[0012] As a preferred solution of the method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the atomizing medium during atomization is nitrogen and the atomizing pressure is 6 bar.

[0013] As a preferred solution of the method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material in the present invention, the concentrations of the metal nitrate and the metal chloride are both 0.3 M.

[0014] Compared with the prior art, the present invention has the following beneficial effects: the present invention utilizes the different condensation rates of zinc atoms and tin atoms during the spraying process, and can directly prepare the zinc stannate nanoheterojunction by only one-step solution precursor plasma spraying, without any template agent, and has fast coating forming speed, simple method, higher bonding strength and faster deposition efficiency; the pore size distribution of the gas-sensitive coating prepared by the present invention presents a bimodal distribution, which can achieve a rapid response to the VOC target gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 It is a schematic diagram of the process of depositing a gas-sensitive coating using the present invention.

[0016] Among them, 1 sensor substrate, 2 gas sensitive coating, 3 atomized droplets, 4 plasma jet, 5 plasma spray gun, 6 precursor liquid storage tank, 7 deionized water storage tank, 8 gas tank.

[0017] Figure 2 The figures are the experimental results of the gas-sensitive material prepared in Example 1; wherein (a) is the pore size distribution curve, (b) is the cross-sectional morphology, and (c) is the room temperature gas-sensitive performance diagram.

[0018] Figure 3 The figures are the experimental results of the gas-sensitive material prepared in comparative example 1 after testing; wherein (a) is the pore size distribution curve, (b) is the cross-sectional morphology, and (c) is the room temperature gas-sensitive performance diagram.

[0019] Figure 4 The figures are the experimental results after testing the gas-sensitive material prepared in comparative example 2; (a) is the pore size distribution curve, (b) is the cross-sectional morphology, and (c) is the room temperature gas-sensitive performance diagram.

[0020] Figure 5 The figures are the experimental results after testing the gas-sensitive material prepared in comparative example 3; wherein (a) is the pore size distribution curve, (b) is the cross-sectional morphology, and (c) is the room temperature gas-sensitive performance diagram.

[0021] Figure 6 This is the pore size distribution curve of the zinc metastannate composite gas-sensitive material in Example 2 of the present invention.

[0022] Figure 7 This is the pore size distribution curve of the zinc metastannate composite gas-sensitive material in Example 3 of the present invention.

[0023] Figure 8 This is the pore size distribution curve of the zinc metastannate composite gas-sensitive material in Example 4 of the present invention.

[0024] Fig. 9 This is the pore size distribution curve of the zinc metastannate composite gas-sensitive material in Example 5 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0028] Zinc nitrate hexahydrate, tin tetrachloride pentahydrate, zinc acetate dihydrate, and sodium stannate tetrahydrate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0029] Example 1 The preparation method of the dual-mesoporous zinc metastannate composite gas-sensitive material of the present invention comprises the following steps: Weigh 0.15 mol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and tin tetrachloride pentahydrate (SnCl4·5H2O) as zinc source and tin source, respectively, dissolve in 500 mL of deionized water solvent, and stir magnetically at room temperature to obtain a homogeneous mixed solution as a liquid precursor; The liquid precursor is pumped out (compressed nitrogen is stored in the gas tank, the precursor liquid storage tank and the deionized water storage tank are closed, and compressed nitrogen is introduced into the precursor liquid storage tank and the deionized water storage tank respectively to push the liquid precursor in the storage tank out through the pipeline), the atomization pressure is 6 bar, and the liquid precursor is sent into the plasma jet at a flow rate of 28 mL / min; After the atomized droplets 3 are heated and accelerated by the plasma flame flow, they condense on the surface of the sensor substrate to form a gas-sensitive coating. During the deposition process, the process parameters are as follows: the argon flow rate is 35 L / min, the hydrogen flow rate is 3 L / min, and the spraying current is 312 A (first, the argon gas is introduced through the periphery of the nozzle to stably cover the high-temperature gas flow around the nozzle to form a protective atmosphere, prevent the atomized droplets from contacting the outside world, and ensure the chemical purity of the material; at the same time, the addition of hydrogen further reduces the oxygen content, so that the liquid precursor remains in a reduced state when being atomized. This atmosphere control can significantly affect the formation and cooling of the droplets, ensuring that the prepared metal oxide particles have the expected microstructure and chemical composition).

[0030] The pore size distribution of the nanostructured gas-sensitive coating was detected using a specific surface area and pore size analyzer (BET). Figure 2 As shown, in addition to the main mesopores at 3.93 nm, the sample also has secondary mesopores at 3.31 nm, indicating that the prepared zinc metastannate composite gas-sensitive material has a dual mesoporous structure.

[0031] Observation of the cross-sectional microstructure of the gas-sensitive coating: The cross-sectional morphology of the nanostructured gas-sensitive coating was detected using a field emission scanning electron microscope (SEM). Figure 2 As shown in b, it is confirmed that the thickness of the prepared gas-sensitive coating is 10 μm.

[0032] Application of gas-sensitive coating in detecting 2-undecanone VOC gas.

[0033] Study on the room temperature gas-sensing performance of gas-sensitive coatings: The room temperature gas-sensing performance of gas-sensitive coatings was tested using a self-made gas-sensing performance test device. Figure 2 c is a room temperature gas-sensing performance diagram of the gas-sensitive coating in this embodiment. Under room temperature conditions, it exhibits the gas-sensitive characteristics of an n-type semiconductor to 2-undecanone VOC gas molecules. When 13 ppm of target gas is introduced, its sensitivity is 11.03.

[0034] Comparative Example 1 This comparative example is based on Example 1. The difference between this comparative example and Example 1 is that the hydrogen flow rate is 5 L / min, the spraying current is 312 A, and the gas-sensitive coating is deposited.

[0035] like Figure 3 As shown, its mesopores are located at 3.14 nm, the double mesoporous structure disappears, the thickness is about 7 μm and the room temperature sensitivity is about 5.16.

[0036] Comparative Example 2 This comparative example is based on Example 1. The difference between this comparative example and Example 1 is that the hydrogen flow rate is 1 L / min, the spraying current is 312 A, and the gas-sensitive coating is deposited.

[0037] like Figure 4 As shown, the main mesopore is located at 3.94 nm, the secondary mesopore is located at 2.97 nm, the thickness is about 20 μm and the room temperature sensitivity is about 3.47.

[0038] Comparative Example 3 This comparative example is based on Example 1. The difference between this comparative example and Example 1 is that the hydrogen flow rate is 7 L / min, the spraying current is 312 A, and the gas-sensitive coating is deposited.

[0039] like Figure 5As shown, the main mesopore is located at 3.07 nm, the double mesopore structure disappears, the thickness is about 5.5 μm and the room temperature sensitivity is about 2.89.

[0040] Example 2 The difference between this embodiment and embodiment 1 is that: Zinc acetate dihydrate (Zn(CHCOO)2·5H2O) was selected as the zinc source to deposit the gas-sensitive coating.

[0041] like Figure 6 As shown, the main mesopore is located at 3.15 nm, the double mesopore structure disappears, the thickness is about 8.6 μm and the room temperature sensitivity is about 3.62.

[0042] Example 3 The difference between this embodiment and embodiment 1 is that: Zinc acetate heptahydrate (ZnSO4·7H2O) was selected as the zinc source to deposit the gas-sensitive coating.

[0043] like Figure 7 As shown, the main mesopore is located at 3.72 nm, the double mesopore structure disappears, the thickness is about 9.2 μm and the room temperature sensitivity is about 2.34.

[0044] Example 4 The difference between this embodiment and embodiment 1 is that: Stannous chloride dihydrate (SnCl2·2H2O) was selected as the tin source to deposit the gas-sensitive coating.

[0045] like Figure 8 As shown, its main mesopore is located at 3.32 nm, the double mesopore structure disappears, the thickness is about 10.7 μm, and the room temperature sensitivity is about 2.91.

[0046] Example 5 The difference between this embodiment and embodiment 1 is that: Sodium stannate tetrahydrate (Na2SnO3·4H2O) was selected as the tin source to deposit the gas-sensitive coating.

[0047] like Fig. 9 As shown, its main mesopore is located at 3.51 nm, the double mesopore structure disappears, the thickness is about 9.6 μm, and the room temperature sensitivity is about 1.98.

[0048] From the above, it can be seen that Example 1 is the best implementation method. The zinc metastannate composite gas-sensitive material is prepared by a template-free method. A special dual-mesoporous pore structure is constructed macroscopically, so that the gas can diffuse more easily on the surface of the gas-sensitive material; microscopically, a heterojunction is formed by only one-step process, which improves the surface energy synthesis activity and increases the adsorption of oxygen molecules. The gas-sensitive material prepared by the prior art scheme has higher sensitivity and selectivity. As a 2-undecanone gas-sensitive sensing material, the dual-mesoporous zinc metastannate composite metal oxide has both macroscopic and microscopic advantages, so it can improve the response value and selectivity of 2-undecanone at room temperature, realize the detection of 2-undecanone, and has a simple structure, low cost, and can be mass-produced. In addition, the preparation method is simple and controllable, and is expected to promote the large-scale application of dual-mesoporous metal oxides in the field of gas sensing.

[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a dual-mesoporous zinc metastannate composite gas-sensitive material, characterized in that: The following steps are included: A homogeneous mixed solution is prepared by a hydrolysis method; The homogeneous mixed solution is transported to the atomizing nozzle through a gas tank, and then injected into the center of the plasma flame after forming droplets; The plasma flame state is controlled by adjusting the hydrogen flow rate and the arc voltage of the spray gun, so that the liquid material is atomized, evaporated and condensed in sequence to form a coating.

2. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to claim 1, characterized in that: The steps for preparing a homogeneous mixed solution are: Two metal oxide precursor liquid materials, metal nitrate and metal chloride, are dissolved in deionized water according to a set ratio, and stirred at room temperature to obtain a homogeneous mixed solution.

3. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to claim 2, characterized in that: The molar ratio of the metal nitrate to the metal chloride is 1:

1.

4. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to claim 3, characterized in that: The metal nitrate and the metal chloride are zinc nitrate hexahydrate and tin tetrachloride pentahydrate respectively.

5. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to any one of claims 1 to 4, characterized in that: The flow rate of the homogeneous mixed solution when conveyed to the atomizing nozzle is 28 mL / min, the argon flow rate is 35 L / min, the hydrogen flow rate is 1-5 L / min, and the spraying current is 312 A.

6. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to claim 5, characterized in that: The atomizing medium during atomization is nitrogen and the atomizing pressure is 6 bar.

7. The method for preparing the dual-mesoporous zinc metastannate composite gas-sensitive material according to claim 3 or 4, characterized in that: The concentrations of the metal nitrate and the metal chloride are both 0.3 M.

Citation Information

Patent Citations

  • Method for synthesizing large-aperture mesoporous bimetallic oxide semiconductor gas-sensitive material

    CN110451561A